Use of Hybrid PEDOT:PSS/Metal Sulfide Quantum Dots for a Hole Injection Layer in Highly Efficient Green Phosphorescent Organic Light-Emitting Diodes - Zhu, Wenqing; Ding, Kuangyu; Yi, Chen; Chen, Ruilin; Wei, Bin; Huang, Lu; Li, Jun (Frontiers in Chemistry, 2021)
In this study, we have synthesized the molybdenum sulfide quantum dots (MoS2 QDs) and zinc sulfide quantum dots (ZnS QDs) and demonstrated a highly efficient green phosphorescent organic light-emitting diode (OLED) with hybrid poly (3,4-ethylenedioxythiophene)/poly (styrenesulfonate) (PEDOT:PSS)/QDs hole injection layer (HIL). The electroluminescent properties of PEDOT:PSS and hybrid HIL based devices were explored. An optimized OLED based on the PEDOT:PSS/MoS2 QDs HIL exhibited maximum current efficiency (CE) of 72.7 cd A−1, which shows a 28.2% enhancement as compared to counterpart with single PEDOT:PSS HIL. The higher device performance of OLED with hybrid HIL can be attributed to the enhanced hole injection capacity and balanced charge carrier transportation in the OLED devices. The above analysis illustrates an alternative way to fabricate the high efficiency OLEDs with sulfide quantum dots as a HIL.